Incretin and Pancreatic β-Cell Function in Patients with Type 2 Diabetes - Chang Ho Ahn; Tae Jung Oh; Se Hee Min; Young Min Cho (Endocrinology and Metabolism, 2023)
To maintain normal glucose homeostasis after a meal, it is essential to secrete an adequate amount of insulin from pancreatic β-cells. However, if pancreatic β-cells solely depended on the blood glucose level for insulin secretion, a surge in blood glucose levels would be inevitable after the ingestion of a large amount of carbohydrates. To avoid a deluge of glucose in the bloodstream after a large carbohydrate- rich meal, enteroendocrine cells detect the amount of nutrient absorption from the gut lumen and secrete incretin hormones at scale. Since insulin secretion in response to incretin hormones occurs only in a hyperglycemic milieu, pancreatic β-cells can secrete a “Goldilocks” amount of insulin (i.e., not too much and not too little) to keep the blood glucose level in the normal range. In this regard, pancreatic β-cell sensitivity to glucose and incretin hormones is crucial for maintaining normal glucose homeostasis. In this Namgok lecture 2022, we review the effects of current anti-diabetic medications on pancreatic β-cell sensitivity to glucose and incretin hormones.